Involvement of PorK, a component of the type IX secretion system, in Prevotella melaninogenica pathogenicity. (4th September 2018) - Kondo, Yoshio; Sato, Keiko; Nagano, Keiji; Nishiguchi, Miyuki; Hoshino, Tomonori; Fujiwara, Taku; Nakayama, Koji
ABSTRACT: Prevotella melaninogenica is a gram‐negative anaerobic commensal bacterium that resides in the human oral cavity and is isolated as a pathogen of suppurative diseases both inside and outside the mouth. However, little is known about the pathogenic factors of P. melaninogenica . The periodontal pathogens Porphyromonas gingivalis and Tanerella forsythia secrete virulence factors such as protease and bacterial cell surface proteins via a type IX secretion system (T9SS) that are involved in pathogenicity. P. melaninogenica also possesses all known orthologs of T9SS. In this study, a P. melaninogenica GAI 07411 mutant deficient in the orthologue of the T9SS‐encoding gene, porK, was constructed. Hemagglutination and biofilm formation were decreased in the porK mutant. Furthermore, following growth on skim milk‐containing medium, the diameters of the halos surrounding the porK mutant were smaller than those of the wild‐type strain, suggesting a decrease in secretion of proteases outside the bacterium. To investigate this in detail, culture supernatants of wild‐type and porK mutant strains were purified and compared by two‐dimensional electrophoresis. In the mutant strain, fewer spots were detected, indicating fewer secreted proteins. In infection experiments, the mortality rate of mice inoculated with the porK mutant strain was significantly lower than in the wild‐type strain. These results suggest that P. melaninogenica secretes potent virulence factors via the T9SS that contribute to its pathogenic ability.